2014
DOI: 10.1039/c4ta01537a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption performance of cross-linked porous polycarbazoles

Abstract: Hypercrosslinked carbazole-based porous organic polymers were prepared via FeCl3-promoted one-step oxidative coupling reaction and Friedel–Crafts alkylation in one pot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 50 publications
10
87
0
2
Order By: Relevance
“…S12, ESI †), which supports the theory that incomplete crosslinking is more likely with higher equivalents of FDA due to incomplete bridge formation between aromatic monomer units; this observation has previously been reported for carbazole based HCPs. 58 The CP MAS NMR for the HCPs prepared with monomers other than toluene showed the same characteristic peaks (Fig. S11b, ESI †).…”
Section: Synthesis Of Hcpsmentioning
confidence: 67%
“…S12, ESI †), which supports the theory that incomplete crosslinking is more likely with higher equivalents of FDA due to incomplete bridge formation between aromatic monomer units; this observation has previously been reported for carbazole based HCPs. 58 The CP MAS NMR for the HCPs prepared with monomers other than toluene showed the same characteristic peaks (Fig. S11b, ESI †).…”
Section: Synthesis Of Hcpsmentioning
confidence: 67%
“…How to use hydrogen in safety state and design a storage material with a high H 2 adsorption capacity is still a challenge . MOPs have exhibited potential in hydrogen storage for their high uptake at 77 K and 1.0 bar, such as PSN‐3 ( S BET = 865 m 2 g −1 , 1.32 wt%), CPOP‐15 ( S BET = 1190 m 2 g −1 , 1.29 wt%), and PPN‐3 ( S BET = 2840 m 2 g −1 , 1.58 wt%) . The hydrogen uptakes of polymers (Figure ) at 77 K/1.0 bar are 1.21, 1.33, 1.28, and 1.22 wt% for PCz–C3–Cz to PCz–C6–Cz, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, significant research efforts have been devoted to the development of carbazole‐based conjugated porous materials. For example, the carbazole–spacer–carbazole‐type conjugated microporous networks showed a high surface area of 1222 m 2 g −1 with an H 2 uptake capacity of 1.66% at 77 K, 1.1 bar; the crosslinked porous polycarbazoles CPOP‐15 exhibited a high amount of toluene adsorbed (about 16.0 mmol g −1 ) at the saturated vapor pressure; the PPTBC based on carbazole building blocks shows the highest CO 2 capture capacity of 2.93 mmol g −1 at 273 K/1.13 bar; the N ‐vinyl carbazole‐based conjugated porous materials P2 exhibited a CO 2 uptake capacity of 12.95 wt% at 1.0 bar and 273 K; and the carbazolic porous of organic framework of Cz‐POF‐3 from a branched carbazole building block gave rise to a high CO 2 uptake capacity of 21.0 wt% at 1.13 bar and 273 K . These results demonstrated that such carbazole‐functionalized MOPs have great potential to increase the gas capture capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, carbazole groups have been widely used in POPs for providing nitrogen-rich functionalized skeleton. [71][72][73][74][75][76][77][78][79] In 2012, a microporous polycarbazole CPOP-1 prepared via carbazole-based oxidative coupling polymerization was reported by Chen et al (Fig. 4).…”
Section: Heteroatomic Skeletonmentioning
confidence: 97%